Benign tumor mimicking cancer in breast: a case report - Ding, Tingting; Zheng, Yu; Zhang, Jianyong; Peng, Yunsong (Frontiers in Oncology, 2025)
Breast granular cell tumor (BGCT) is a rare neoplasm that typically presents as a benign lesion but is frequently misdiagnosed as breast cancer prior to biopsy. Herein, we report a case of BGCT that was initially suspected to be breast cancer based on preoperative physical examination and imaging findings. A 39-year-old Asian woman presented with a firm and painless mass in the right breast. Color Doppler ultrasonography revealed a 15 mm × 15 mm × 14 mm nodule in the upper inner quadrant of the right breast without obvious blood flow signal. On magnetic resonance imaging (MRI), dynamic contrast-enhanced sequences demonstrated homogeneous enhancement. Both ultrasonography and MRI reported the lesion as the Breast Imaging Reporting and Data System (BI-RADS) Category 4B. Based on these findings, the patient was clinically suspected to be an early breast cancer. A surgical plan was formulated, beginning with an excisional frozen section with negative margins and proceeding to breast-conserving surgery if necessary. Frozen section analysis confirmed the presence of a tumor but could not determine whether the lesion was benign, malignant, or borderline. Histopathological examination with hematoxylin-eosin staining and immunohistochemistry ultimately established the diagnosis of BGCT. Early and accurate diagnosis is crucial for developing appropriate treatment plans for breast neoplasms. Given the unique characteristics and rarity of these tumors, clinicians, radiologists and pathologists should remain vigilant and consider the possibility of BGCT in the differential diagnosis.